2019
DOI: 10.1136/tobaccocontrol-2018-054796
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine arms race: JUUL and the high-nicotine product market

Abstract: ObjectiveUntil recently, purveyors of vaping products marketed e-liquids in the 1%–3% range of nicotine concentration with those at 3% described as ‘super high’ intended for two packs/day smokers. The goal of this study is to evaluate the degree to which JUUL, with its 5% nicotine and 75% US market share, has spurred other e-liquid vendors to raise the nicotine levels of their products.MethodsOnline search to identify brands offering e-liquid in exceptionally high nicotine concentration (≥5%) and to catalogue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
133
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(154 citation statements)
references
References 22 publications
1
133
1
3
Order By: Relevance
“…For example, the addictive potential of nicotine salts may have contributed to the dramatic recent increase in 2018 in vaping among young people in the US, fueled by Juul. However, this addictive potential may be more satisfying to smokers who are switching to e-cigarettes 19. We note, however, that whereas Juul are currently sold with 59 mg/mL of nicotine salt in the US, they can be sold only with 18 mg/mL in the UK.…”
Section: Challenges and Guidelines For Cliniciansmentioning
confidence: 92%
See 1 more Smart Citation
“…For example, the addictive potential of nicotine salts may have contributed to the dramatic recent increase in 2018 in vaping among young people in the US, fueled by Juul. However, this addictive potential may be more satisfying to smokers who are switching to e-cigarettes 19. We note, however, that whereas Juul are currently sold with 59 mg/mL of nicotine salt in the US, they can be sold only with 18 mg/mL in the UK.…”
Section: Challenges and Guidelines For Cliniciansmentioning
confidence: 92%
“…The nicotine concentration in US marketed Juul liquid cartridges (pods) is higher (5% weight/weight; 59 mg/mL; 127 mM) than in traditional e-liquids (typically 6-18 mg/mL of nicotine; 37-111 mM). Recent studies have shown that Juul users have similar blood nicotine concentration profiles to users of combustible cigarettes 19…”
Section: Device Evolution and The Rise Of Juulmentioning
confidence: 99%
“…One product frequently mentioned was salt nicotine e-liquid. Compared to traditional e-liquids, salt nicotine e-liquids allow users to vape higher nicotine strengths while experiencing a less harsh throat hit [13]. Due to its high nicotine content, it also mimics the sensation of smoking a combustible cigarette.…”
Section: E-liquidsmentioning
confidence: 99%
“…JUUL, a new ENDS product, provides a high amount of nicotine, with one "vape pod" containing a comparable amount of nicotine as a pack of cigarettes [4]. JUUL has exploded in popularity because it was first introduced to the U.S. market in 2015, now accounting for roughly 75% of sales in the ENDS retail market as measured through convenience store data [5]. Many in the public health community believe the rise of JUUL is largely responsible for the increase in ENDS product use among young people [3,6].…”
mentioning
confidence: 99%